An-Nuṣūṣ al-‘Arabiyyah dhāt al-Mawḍū‘ al-Bī’ī bi-Waṣfihā Wasīlah li-t-Tarbiyah al-ʾĪkūlūjiyyah fī Ta‘līm al-Lughah al-‘Arabiyyah: Arabic Texts with Environmental Themes as a Means of Ecological Education in Teaching the Arabic Language - Rahman, Muhammad Amin Abdul (Critical Review of English-Arabic World Journal, 2025)
يهدف هذا البحث إلى الكشف عن دور النصوص العربية ذات الموضوع البيئي في تعزيز الوعي الإيكولوجي لدى المتعلمين، إضافة إلى إمكان توظيفها بوصفها مادة تعليمية في سياق تعليم اللغة العربية. وقد اعتمد البحث منهج الدراسة المكتبية بأسلوب نوعي لتحليل مجموعة من النصوص البيئية والكشف عن القيم والمفاهيم التي تتضمنها. وأظهرت النتائج أنّ هذه النصوص تحمل جملة من الرسائل التربوية التي تعزز الشعور بالمسؤولية تجاه البيئة، كما تمتلك قدرة واضحة على تنمية مهارات القراءة والمفردات لدى المتعلمين. ويخلص البحث إلى أنّ دمج النصوص البيئية في تعليم اللغة العربية يمكن أن يسهم في تحقيق تكامل بين الأهداف اللغوية والبيئية في آن واحد. This study aims to uncover the role of Arabic texts with environmental themes in enhancing ecological awareness among learners, as well as their potential use as educational material in the context of teaching the Arabic language. The research adopts a qualitative library-based approach to analyze a selection of environmental texts and identify the values and concepts they contain. The findings show that these texts carry a number of educational messages that strengthen the sense of responsibility toward the environment, and they clearly have the ability to develop learners’ reading skills and vocabulary. The study concludes that integrating environmental texts into Arabic language instruction can contribute to achieving a balance between linguistic and environmental objectives simultaneously.